2013
DOI: 10.18268/bsgm2013v65n2a15
|View full text |Cite
|
Sign up to set email alerts
|

The bathyal decapod crustacean community from the Poggio i Sodi quarries (Siena Basin, Tuscany, Italy)

Abstract: A rich decapod fauna from the Early Pleistocene (late Gelasian-early Calabrian) of Poggio i Sodi quarries (Siena, Tuscany, central Italy) is here reported. Integrated biostratigraphical, sedimentological and paleoecological analyses have been carried out, and some paleoenvironmental inferences are also proposed. The studied decapod community is herein assigned to the upper bathyal; several paleoenvironmental factors (cool water conditions at the sea floor, clay soft bottom, nutrients, very low environmental en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 35 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…These characters and the shape and arrangement of the pleonal sternites (where observables) allow ascribing the specimens to the fossil and extant G. rhomboides. This species has been already reported from the Pliocene-Pleistocene of Piedmont, Emilia Romagna, Tuscany, and Lazio (Ristori, 1891b;De Angeli et al, 2009;Baldanza et al, 2013).…”
Section: Chlinocephalus Demissifronsmentioning
confidence: 67%
See 2 more Smart Citations
“…These characters and the shape and arrangement of the pleonal sternites (where observables) allow ascribing the specimens to the fossil and extant G. rhomboides. This species has been already reported from the Pliocene-Pleistocene of Piedmont, Emilia Romagna, Tuscany, and Lazio (Ristori, 1891b;De Angeli et al, 2009;Baldanza et al, 2013).…”
Section: Chlinocephalus Demissifronsmentioning
confidence: 67%
“…Monodaeus bortolottii has been previously reported only from the Pliocene of Volterra (Delle Cave, 1988) and Grosseto (De Angeli et al, 2009) in Tuscany. Finally, according to Baldanza et al (2013) this species is also reported from the Early Pleistocene of Poggio i Sodi (Siena, Tuscany). This is the first record of this species from Emilia Romagna Region (N Italy).…”
Section: Monodaeus Bortolottiimentioning
confidence: 83%
See 1 more Smart Citation
“…; Baldanza et al . ). The Miocene occurrences comprise Retropluma borealis from Denmark (Fraaije et al .…”
Section: Discussionmentioning
confidence: 97%
“…Genus survived in the Mediterranean until the Pliocene and Pleistocene with R. craverii known from Italy (Crema, 1895;BalDanZa et al, 2013). The Miocene occurrences comprise of Retropluma slovenica from Early Miocene of Slovenia (Gašparič & Hyžný, 2015) and Middle Miocene of Slovakia (Hyžný et al, 2015), Retropluma borealis from Late Miocene of Denmark (Fraaije et al, 2005), and Retropluma laurentae from Late Miocene of Sabakh, Borneo (Collins et al, 2003).…”
Section: Palaeobiogeographymentioning
confidence: 99%